Sufi Values in the Characterization of the Pandowo Limo Wayang Figures - Badrut Tamam Qomaruddin; Dianing Pra Fitri (Universitas Syiah Kuala, 2025)
This study explores the Sufi values embedded in the characterization of the Pandowo Limo figures in Javanese wayang. The research aims to provide a deeper understanding of these figures so that society does not merely perceive them as entertainment but also as a source of guidance. Misinterpretations and alterations of the essence of the Pandowo Limo characters often occur, diminishing their intended philosophical and spiritual significance. This study employs a qualitative research approach using library research methods. Through this approach, the meanings and interpretations of wayang as established by the Wali Songo are aligned with Islamic theological teachings (aqidah) and Sharia principles in Java. The Wali Songo utilized wayang not only as a means of preserving Javanese culture but also as a medium to integrate Islamic beliefs into local traditions. By embedding Islamic values within wayang, they aimed to prevent misconceptions and ensure that the practice of Javanese culture remained in harmony with Islamic teachings.